Gelcasting as a Novel Processing Route to Fabricate PartiallyStabilized Zirconia Ceramic Bodies: Gelcasting ceramic bodiesprocess - Sahraei Khanghah, Nasim; Faghihi-Sani, Mohammad-Ali; Kamali, Alireza; Sadeghian, Zahra (Iranian Journal of Pharmaceutical Sciences, 2008)
Bioinert ceramics, like alumina and zirconia are used mainly for replacementsof bones, hip joints and for dental implants. Partially stabilized zirconia ceramics(PSZ or TZPwith 3 mol.% or 5 wt.% Y2O3), appear as perspective bioinert ceramicsbecause of their high strength and corrosion resistance. In order to fabricate complexshapes, it is essential to use a near net shape processing like gelcasting as anuncomplicated method which has appropriate potential of producing special shapeswith suitable green and sintered properties (like high mechanical properties and almostfull density and machinability of green bodies). Moreover, biocompatibility studieshave proved that this processing route is nontoxic. In this experiment, micro-structural observation performed to illustrate the effect of dispersant on homogeneityof gelcast 3Y-TZPbodies. It has been shown that it is possible to achieve uniformmicrostructure by means of appropriate amount of dispersant and ultrasonic wave.In addition, the machinability of these green bodies has been proven and somecomplex shaped bodies fabricated, in order to illustrate the capability of the process.